2017
DOI: 10.1016/j.injury.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of non-return to work 2 years post-injury in road traffic crash survivors: Results from the UQ SuPPORT study

Abstract: Non-return to work following road traffic crash 2 Abstract Purpose: Individuals who have sustained an injury from a road traffic crash (RTC) are at increased risk for long lasting health problems and non-return to work (NRTW). Determining the predictors of NRTW is necessary to develop screening tools to identify at-risk individuals and to provide early targeted intervention for successful return to work (RTW). The aim of this study was to identify factors that can predict which individuals will not RTW followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
(122 reference statements)
2
16
1
Order By: Relevance
“…Moreover, we were not able to assess HRQoL over several time points; hence, we cannot draw conclusions on the change of QoL over the study period. Although this study presented limitations regarding the HRQoL measure, the results concur with previous findings that there is a negative association between the number of SA days and a lower HRQoL 10–12…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, we were not able to assess HRQoL over several time points; hence, we cannot draw conclusions on the change of QoL over the study period. Although this study presented limitations regarding the HRQoL measure, the results concur with previous findings that there is a negative association between the number of SA days and a lower HRQoL 10–12…”
Section: Discussionsupporting
confidence: 90%
“…Studies have identified a varying rate of individuals who report sickness absence (SA) or have a delayed or failed return to work following RTI, that is, a resumption of SA after a return to work, (ranging from 14% to 42%) 6–9. Persons who have a greater number of SA days and have a delayed or failed return to work report significantly lower self-reported health compared with their counterparts 10–13…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…government legislation). At the individual level, self-rated health [28], disability level [29], recovery expectations [28, 29], job type [28, 30], and work hours [28] of injured individuals have been associated with return to work rates after a road traffic crash and may also be associated with return to work rates and other work-related outcomes following an intervention.…”
Section: Introductionmentioning
confidence: 99%